Norlichexanthone purified from plant endophyte prevents postmenopausal osteoporosis by targeting ERα to inhibit RANKL signaling - Keqi Wang; Yongyan Chen; Shuo Gao; Maosi Wang; Mengmeng Ge; Qian Yang; Mingkai Liao; Lin Xu; Junjie Chen; Zhiping Zeng; Haifeng Chen; Xiao-kun Zhang; et al. (Elsevier, 2021)
Although different types of drugs are available for postmenopausal osteoporosis, the limitations of the current therapies including drug resistances and adverse effects require identification of novel anti-osteoporosis agents. Here, we defined that norlichexanthone (NOR), a natural product, is a ligand of estrogen receptor-alpha (ERα) and revealed its therapeutic potential for postmenopausal osteoporosis. We used mammalian-one hybrid assay to screen for ERα modulators from crude extracts of several plant endophytes. As a result, NOR purified from the extract of endophyte ARL-13 was identified as a selective ERα modulator. NOR directly bound to ERα with an affinity in nanomolar range, revealing that it is a natural ligand of ERα. NOR induced osteoblast formation in MC3T3-E1 precursor cells. Conversely, NOR inhibited receptor activator of nuclear factor-kappa B ligand (RANKL)-induced osteoclast formation in both RAW264.7 macrophages and mouse primary monocytes. Mechanistically, NOR inhibited RANKL-induced association of ERα and TRAF6 to prevent ERα-mediated TRAF6 activation via Lys63-linked ubiquitination. Importantly, NOR exhibited potent anti-osteoporosis efficacy in an ovariectomized mouse model. Comparing to estrogen, NOR was of much less capability in stimulating endometrial hyperplasia and promoting mammalian cancer cell proliferation. Taken together, our study identified NOR as a natural and high affinity ligand of ERα with substantial anti-osteoporosis but less estrogenic activity.